2005
DOI: 10.1007/s10641-004-9077-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fish density, assemblage composition and relative rates of predation among mangrove, seagrass and coral reef habitats

Abstract: We tested the hypothesis for several Caribbean reef fish species that there is no difference in nursery function among mangrove, seagrass and shallow reef habitat as measured by: (a) patterns of juvenile and adult density, (b) assemblage composition, and (c) relative predation rates. Results indicated that although some mangrove and seagrass sites showed characteristics of nursery habitats, this pattern was weak. While almost half of our mangrove and seagrass sites appeared to hold higher proportions of juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 39 publications
6
49
2
Order By: Relevance
“…The presence of adult fish in all sampled habitats was consistent with Sheaves (2005) and Chittaro et al (2005) conclusions that the term 'nursery area' applied for mangroves and seagrass habitats should be used with discretion. Based in our results, we consider the term 'adult habitat' applied for coral reefs should be used also with discretion.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The presence of adult fish in all sampled habitats was consistent with Sheaves (2005) and Chittaro et al (2005) conclusions that the term 'nursery area' applied for mangroves and seagrass habitats should be used with discretion. Based in our results, we consider the term 'adult habitat' applied for coral reefs should be used also with discretion.…”
Section: Discussionsupporting
confidence: 83%
“…Aguilar-Perera & Appeldoorn (2007) found significant differences among habitats for S. aurofrenatum and S. viride juveniles, but not for S. iseri juveniles. The preference of S. aurofrenatum and S. iseri for reef habitats has also been reported by others (Adams & Ebersole, 2002;Chittaro et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several studies have shown clear effects of the presence of seagrass beds or mangroves on fish assemblages on coral reefs, suggesting a high dependence of some species on these habitats, either at the scale of multiple islands , Halpern 2004 or of single islands (Serafy et al 2003, Dorenbosch et al 2004, Mumby et al 2004). However, Chitaro et al (2005) found substantial variation between sites in the abundance of juvenile fishes, indicating that not all seagrass beds and mangroves function equally as juvenile habitats. These results caution against the generalisation that all mangrove and seagrass habitats have a similar function as a juvenile fish habitat.…”
Section: Introductionmentioning
confidence: 92%